LDL Lowering with Statins in Diabetes - Gordon, Debra (MD Conference Express, 2010)
Cardiovascular disease (CVD) is the primary cause of morbidity and mortality in people with diabetes, accounting for 70% of all deaths [Lloyd-Jones D et al. Circulation 2009]. Individuals with diabetes experience an enhanced atherosclerotic process, resulting in an increased plaque burden that affects smaller blood vessels, an increased necrotic core within the plaque, and greater macrophage and T-cell infiltration, all of which increase plaque vulnerability to rupture and result in thrombosis [Ross R et al. N Engl J Med 1999].